Geographical variations and potential low-value neuroimaging examinations in Norway from 2013 to 2022 - Brandsæter, Ingrid Øfsti; Porthun, Jan; Andersen, Eivind Richter; Hofmann, Bjørn Morten; Kjelle, Elin (Research in Health Services & Regions, 2025)
Purpose To investigate the variations in the use of neuroimaging over time and across geographical regions and to investigate the use of two potential low-value neuroimaging examinations for all imaging in an entire country (Norway), including both inpatient and outpatient services from 2013 to 2022. Method and methods Data on neuroimaging for outpatients was collected from the Norwegian Health Economics Administration, and inpatient data were collected from individual Hospital Trusts (HT) in Norway. The data were analysed using descriptive statistics. Results On average, 413,303 (786 per 10,000 inhabitants) neuroimaging examinations were performed annually in Norway. Overall, the use increased by 16% during the study period. Substantial geographical variations were found both in general and for the two potential low-value neuroimaging examinations; Brain Magnetic Resonance Imaging (MRI) and Head Computed Tomography (CT). For general neuroimaging, the HT with the highest use performed twice as many examinations as the HT with the lowest use per inhabitant. For the potential low-value neuroimaging examinations, the HTs with the highest use performed two and three times as many examinations as the HTs with the lowest use per inhabitant. Conclusion There was temporal and geographical variation in the general use of neuroimaging and the use of the two potential low-value examinations, Brain MRI and Head CT. In Norway, the estimated annual cost of low-value neuroimaging examinations is about EUR 4.0 million. Reducing the use of low-value imaging would free up resources for examinations of high value.